ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PENGGUNA JASA BARBERSHOP DI KECAMATAN SINGAPARNA KABUPATEN TASIKMALAYA - Agus Ahmad Nasrulloh; Ikhsanul Fadillah (Universitas Siliwangi, 2019)
Barbershop business in Tasikmalaya District is increasingly prevalent, including in Singaparna District, but not all Barbershop in Singaparna District are visited by consumers. Competition between Barbershop is found in excellent service quality for consumers, the application of a quality service affects the development of customer satisfaction. The research method used is descriptive method with a qualitative approach. Data is obtained through direct interviews with owners of barbershop and consumers. Then the data is analyzed through the stages of data reduction or simplification, data presentation / presentation (Data Display), and drawing conclusions. The results showed that the quality of services provided in five Barbershop in Singaparna Subdistrict, Tasikmalaya Regency was quite good, this can be seen from the efforts made such as prioritizing appearance, neatly arranged facilities, tools that are always ready to use and choosing a strategic place. The reliability and responsiveness of barbershop can be seen from the consumer's assessment of indicators of reliability, responsiveness, empathy and assurance from Barbershop which is quite good.